Exploring Gendered Drivers of Public Participation in Voluntary Carbon Offset: Evidence from Indonesia - Ardinanta, Rizki; Muhammad Setiadi, Bara; Kevin Alwafi, Muhammad; Dwi Lestari, Rizky (Indonesian Association for Public Administration (IAPA), 2024)
Climate change mitigation through Voluntary Carbon Offset (VCO) initiatives is trending globally, but gender's role in shaping public participation remains underexplored, especially in Indonesia. Therefore, the motivations driving men and women to participate in carbon offset programs need further investigation. This research aims to address the gap in Indonesia by analysing the gender-based differences in public behaviour towards VCO initiatives. The study seeks to identify the key drivers behind Willingness to Offset (WTO) among men and women, contributing insights for developing targeted strategies to promote broader public engagement in carbon offset programs. A quantitative approach was applied, combining descriptive analysis and ordered logistic regression models. Data were gathered from an online national survey of 868 respondents, weighted by gender, education, income, and age to represent the Indonesian population. Six variables were assessed: Knowledge (KNL), Attitude (AT), Social Norms (SN), Perceived Behavioral Control (PBC), and Personal Moral Norms (PMN). The findings reveal significant gender differences in the variables influencing WTO. For men, PBC and PMN were the primary determinants, while women were more motivated by PMN, with SN also playing a strong role. Despite lower scores in knowledge and attitudes, women exhibited higher willingness to offset compared to men. The study concludes that women are primarily driven by moral and social motivations, whereas men are influenced more by knowledge and perceived control over their actions. These insights suggest that gender-sensitive policies and communication strategies are necessary to enhance public participation in VCO initiatives. Understanding these differences can help design more effective programs to support Indonesia's net zero commitment in combating climate change.